2019
DOI: 10.1161/circep.119.007284
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Estimation Using Artificial Intelligence From Standard 12-Lead ECGs

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
250
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(273 citation statements)
references
References 16 publications
19
250
3
1
Order By: Relevance
“…Removing EOG and ECG artifacts mostly reduced performance suggesting that age-related information was present in EOG and ECG. For example, one can easily imagine that older subjects produced less blinks or showed different eye-movement patterns (Thavikulwat et al, 2015) and also cardiac activity may change across the lifespan (Attia et al, 2019).…”
Section: How Important Is Preprocessing For Cross-subject Prediction?mentioning
confidence: 99%
“…Removing EOG and ECG artifacts mostly reduced performance suggesting that age-related information was present in EOG and ECG. For example, one can easily imagine that older subjects produced less blinks or showed different eye-movement patterns (Thavikulwat et al, 2015) and also cardiac activity may change across the lifespan (Attia et al, 2019).…”
Section: How Important Is Preprocessing For Cross-subject Prediction?mentioning
confidence: 99%
“…5,6,8 There have been several studies that challenged to predict BA or "heart age" using ECG. [9][10][11] Moreover, it has been reported that there is a discrepancy between BA estimated by ECG and the actual CA, 9 which could be related to individual physical conditions and also various cardiovascular diseases. This concept could be utilized to the simple method of screening for the patient health status, but for actual clinical use, we may have to consider the racial difference in the performance for the prediction models of BA.…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, so far, most of the models have developed with only several representative ECG parameters by linear regression model, 10,12 and in only one report, arti cial intelligence modeling was applied. 9 In the present study, we developed a prediction model for BA with hundreds of automatically measured ECG parameters by principal component analysis (PCA) algorithm 4 using a single-center cohort in a Japanese cardiovascular hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Hand motion recognition [9][10][11][12][13][14][15][16][17], Muscle activity recognition [18][19][20][21][22][23] ECG Heartbeat signal classification , Heart disease classification [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], Sleep-stage classification [64][65][66][67][68], Emotion classification [69], age and gender prediction [70] EEG Brain functionality classification , Brain disease classification , Emotion classification [122][123][124][125][126][127][128][129], Sleep-stage classification [130][131][132][133]…”
Section: Emgmentioning
confidence: 99%